How to write a systematic review: Tips and tricks for surgeons in training. (March 2017) - Jones, Patrick; Ewan, Helen; Lane, Timothy; Adshead, Jim; Vasdev, Nikhil; Rai, Bhavan Prasad
Systematic reviews provide high-quality critical appraisal and evidence-based summaries on a topic. They represent a key resource for time-pressured clinicians as they strive to deliver better patient care. Robust methodology and adhering to rigorous standards forms the foundation of this type of article. As such, writing a systematic review can prove a great challenge. This article aims to provide an overview of the methodology as well as certain tips and tricks which will help the surgeon when taking on such a project.